The Relevance of Taufiq Ismail's "Qira'atul- 'Alamat" in Enforcing The Character of The Indonesian Nation - Eva Farhah; Alifa Tsamratuz Zahirah; Firman Bagus Saputra; Nur Aulia Adilahanif (CMES (Center of Middle Eastern Studies), 2022)
The objective of this study is to determine the relevance of Taufiq Ismail's poem "Qira'atul-'Alamat," which appears in a collection of poems titled "Turab Fawqa Turab." To reveal the poem's relevance, the meaning of the poem text must first be revealed through heuristic and hermeneutic readings within the framework of semiotic theory, which is a discipline that examines the signs on an object to determine the meaning described in it. These symbols can be found in the text "Qira’tul-‘Alamat" A qualitative descriptive method was chosen to reveal the results of this study. A qualitative descriptive method was chosen to reveal the results of this study. The results of this study revealed that the poetry data has meaning, indicating that humans should always be self-aware, interpret God's signs, and reflect on their actions, attitudes, and words. Man 'amila shaliha falinafsih, wa man sa-a fa'alaiha is thus the foundation of a true life. Humans have previously been shown signs of the presence of an event in order to plan alternative choices that are in compliance with religious teachings and life norms, in expressing words or thinking about, and implemented in everyday life.